Type Design of Control System in Hydroponic Plants Based on Arduino Uno - Arnawan Hasibuan; Rita Sovianto; Ezwarsyah; Asri; Taufiq; M. Sayuti (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The decreasing availability of agricultural land due to urbanization threatens farmers' income and agricultural sustainability. Hydroponic cultivation offers a solution by maximizing limited land, especially in urban areas. However, challenges in managing nutrients and watering systems remain a key research focus to enhance hydroponic efficiency and support environmental sustainability and food security. This research aims to control water flow, watering, and nutrition based on a schedule regulated by the RTC DS3231 and to manage the water volume in the reservoir using the HC-SR04 sensor. Based on data analysis and testing, it is concluded that the system operates effectively, regulating water flow from 08:00 to 17:00 at a flow rate of 0.001464 m³/s, watering pests at 09:00 and 17:00 for 5 minutes at a flow rate of 0.0016 m³/s, providing nutrients every three days at noon for 2 minutes at a flow rate of 0.0007917 m³/s, and managing water volume in the reservoir between a minimum of 92% and a maximum of 97%, with a total capacity of 5,214 liters. This system works well, allowing the owner/farmer to only monitor the hydroponic plants.